ANALISIS PENCAPAIAN KREATIFITAS ANAK USIA DINI MELALUI PEMBELAJARAN TERPADU - Evi Gusniati Rahayu; Siti Badriah (Journal on Education, 2021)
This study aims to determine the improvement of early childhood creativity through integrated learning. Integrated Learning is learning that integrates various aspects of learning using thematic approaches. To achieve aspects of child development optimally, the material presented is explained based on themes and sub-themes. This research method is a qualitative description, this research was conducted in TK Smart Kids. Qualitative data were analyzed using inductive processes with data reduction and data presentation in accordance with themes, and components. The population and sample of this study were children of kindergarten class B Smart Kids, West Bandung Regency. Early childhood creativity can be improved by implementing simple and practical steps in an integrated manner based on integrated learning, through stimulation of creativity learning so the creativity of early childhood can increase eight times higher through real practice making products of creativity. The results of this study are to find out whether children's achievement can be achieved or not. Furthermore, this research is part of the thesis that I will examine.